2007
DOI: 10.2151/sola.2007-006
|View full text |Cite
|
Sign up to set email alerts
|

Tornado Generation in a Narrow Cold Frontal Rainband -Fujisawa Tornado on April 20, 2006-

Abstract: At noon on April 20, 2006, a wind storm occurred in Fujisawa City, Kanagawa Prefecture, Japan with a F0-P1-P1 rank on the Fujita-Pearson-scale (FPP-scale). Damage to over 40 residential buildings was observed. The damage covered an area 2 km by 50 m. The strong winds were accompanied by the passage of a cold front. Eyewitness accounts of a dust column and the recording of a pressure drop (1.5 hPa) indicate the existence of a tornado vortex. A hook-shaped radar echo (5 km in diameter) was observed in the narrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…A key case study is that of Carbone (1982Carbone ( , 1983 in which observations by multiple Doppler radars were synthesized to portray the parent circulation of a tornado on an intense cold front with gravity-currentlike characteristics. Kobayashi et al (2007) reported radar observations of a tornado along a cold-frontal rain band with core/gap structure in Japan. They found that the parent misocyclone had a diameter of 2 km and vorticity of the order of 10 −2 s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…A key case study is that of Carbone (1982Carbone ( , 1983 in which observations by multiple Doppler radars were synthesized to portray the parent circulation of a tornado on an intense cold front with gravity-currentlike characteristics. Kobayashi et al (2007) reported radar observations of a tornado along a cold-frontal rain band with core/gap structure in Japan. They found that the parent misocyclone had a diameter of 2 km and vorticity of the order of 10 −2 s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Fujisawa City is located approximately 25 km from the NDA radar site in Yokosuka (Fig. 1), and a tornado was observed over Fujisawa at the passage of the NCFR (Kobayashi et al 2007a).…”
Section: Observationsmentioning
confidence: 99%
“…However, despite employing such technology, relatively fewer Doppler radar observations of the occurrence and spatial characteristics associated with tornado development of along an NCFR have been conducted to date. Using radar observations, Kobayashi et al (2007a) described a tornado that formed in the NCFR from a parent misocyclone having a diameter of 2 km and a vorticity in the order of 10 À2 s À1 . In Japan, supercell tornadoes accompanying mesocyclones in the parent cloud have been reported (e.g., Niino et al 1993;Kobayashi et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Several case studies of tornadoes that have occurred in the Kanto region have been published (e.g., Niino et al 1993;Suzuki et al 2000;Kobayashi et al 2007), and Sugawara and Kobayashi (2008) used Doppler radar data and photographs of the funnel cloud to analyze a waterspout that occurred over Tokyo Bay.…”
Section: Introductionmentioning
confidence: 99%